Preparation method and application of Ge-doped ZnSn (OH) 6 photocatalyst

By hydrothermal synthesis of Ge doped ZnSn(OH)6 photocatalyst, using Ge ions to excite electron-hole pair separation and transfer, the problem of ZnSn(OH)6 photocatalyst in the prior art is solved, and the problem of rapid removal of toluene is achieved. Highly efficient toluene removal and stable catalytic properties.

CN119175093AActive Publication Date: 2024-12-24CHONGQING TECH & BUSINESS UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411407156.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-24
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing ZnSn(OH)6 photocatalysts are difficult to achieve the complete removal of toluene quickly and effectively in photocatalytic reactions, and the doping strategy is limited.

Method used

Ge ions were introduced through hydrothermal synthesis to prepare Ge doped ZnSn(OH)6 photocatalyst. Ge ions were used to excite electron-hole pair separation and transfer under light irradiation, resulting in a large number of hydroxyl radicals, thereby achieving efficient removal of toluene .

Benefits of technology

Complete removal of toluene in a short period of time improves photocatalytic activity and stability, and provides more effective measures to control environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175093A_ABST
    Figure CN119175093A_ABST
Patent Text Reader

Abstract

The invention relates to the field of photocatalytic materials, and discloses a preparation method and application of a Ge-doped ZnSn (OH) 6 photocatalyst. According to the preparation method, SnCl4. 5H2O, Zn (Ac) 2.2 H2O, alkali metal hydroxide, methyl cellulose and GeO2 are taken as raw materials, and the Ge-doped ZnSn (OH) 6 photocatalyst is prepared in a hydrothermal synthesis mode. Crystalline powder can be obtained without high-temperature sintering, and the catalyst can generate a large number of electrons and hydroxyl radicals, has an excellent degradation effect on volatile organic compounds such as methylbenzene, can achieve a 100% removal effect on methylbenzene with the concentration of 50 ppm within 10 min, has excellent deep mineralization ability, and has good application prospects in pollution prevention and control of the atmospheric environment. Great potential is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photocatalytic materials, and specifically to a preparation method and application of a Ge-doped ZnSn(OH)6 photocatalyst. Background Art

[0002] Zinc hydroxystannate (ZnSn(OH)6) is a mixed metal oxide and a transition metal hydroxide with a large specific surface area and a unique electronic structure. It has a wide band gap and a crystal structure that is conducive to the transmission of electrons. It has high chemical stability during the photocatalytic reaction and is not easily corroded or decomposed. These advantages make zinc hydroxystannate have broad application prospects in environmental pollution control, photocatalytic water decomposition to produce hydrogen, air purification and other fields.

[0003] The preparation methods of ZnSn(OH)6 currently include solvothermal method, hydrothermal method, coprecipitation method, etc. These methods optimize the photocatalytic performance by controlling the crystal form, particle size and morphology of the material. In the current research progress, the most in-depth research is to adjust the band gap of ZnSn(OH)6 by doping, to improve the separation efficiency of photogenerated electron-hole pairs by constructing heterostructures, and to increase the specific surface area by nanostructure regulation. However, the photocatalysts prepared by these modification strategies cannot quickly and effectively achieve the complete removal of toluene.

[0004] Therefore, there is an urgent need to develop a photocatalyst preparation method with better product performance. Summary of the invention

[0005] Technical issues

[0006] Provided is a preparation method for a ZnSn(OH)6-doped Ge ion photocatalyst. The prepared ZnSn(OH)6 can more effectively stimulate the separation of electron-hole pairs and accelerate the transfer of electrons under light irradiation, and can also generate more hydroxyl radicals with H2O, thereby achieving rapid and complete removal of toluene in a short time.

[0007] Technical Solution

[0008] The first aspect of the present application provides a method for preparing a Ge-doped ZnSn(OH)6 photocatalyst, comprising: using SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, methyl cellulose and GeO2 as raw materials, and preparing a Ge-doped ZnSn(OH)6 photocatalyst by hydrothermal synthesis.

[0009] In some embodiments, the specific preparation steps of Ge-doped ZnSn(OH)6 photocatalyst are as follows:

[0010] a. Add SnCl4·5H2O, Zn(Ac)2·2H2O, alkali metal hydroxide, methyl cellulose and GeO2 to distilled water and stir to obtain a mixed solution;

[0011] b. placing the mixture in a sealed pressure vessel for a hydrothermal reaction, and after the reaction is completed, cooling to room temperature, washing, drying and grinding to obtain Ge-doped ZnSn(OH)6 photocatalyst crystalline powder.

[0012] In some embodiments, the alkali metal hydroxide is NaOH, KOH, LiOH.

[0013] Furthermore, the alkali metal hydroxide is NaOH.

[0014] In some embodiments, the molar ratio of SnCl4·5H2O, Zn(Ac)2·2H2O, alkali metal hydroxide, and GeO2 is 1:1-1.2:7-8.4:0.07-4.8.

[0015] Furthermore, the molar ratio of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and GeO2 is 1:1~1.2:7~8.4:0.12~4.8.

[0016] Furthermore, the molar ratio of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and GeO2 is 1:1:7:0.6.

[0017] In some embodiments, the stirring conditions are specifically: 500-800 r / min; 10-20 min.

[0018] In some embodiments, the temperature of the hydrothermal reaction is increased from room temperature to 160° C. to 165° C., and then kept at this temperature for 390 min to 400 min.

[0019] Furthermore, the temperature of the hydrothermal reaction was increased from room temperature to 160° C. and then kept at that temperature for 390 min.

[0020] In some embodiments, the specific steps of washing are: cooling to room temperature and washing with distilled water and anhydrous ethanol twice each.

[0021] In some embodiments, the drying conditions are specifically: drying at 55° C. to 65° C. for 6 to 8 hours.

[0022] The second aspect of the present application provides the use of a Ge-doped ZnSn(OH)6 photocatalyst prepared by the preparation method described in the present application in removing toluene pollutants or preparing a photocatalytic product for removing toluene pollutants.

[0023] Technical Effects

[0024] At present, there are studies on ZnSn(OH)6 doped with elements such as C and S, but there is no research on the application of Ge element to modified ZnSn(OH)6 photocatalyst. The Ge-doped ZnSn(OH)6 photocatalyst prepared by hydrothermal synthesis in this application can obtain crystalline powder without high-temperature sintering. Under light irradiation, a large number of electrons and hydroxyl radicals can be generated in a short time, achieving efficient removal of volatile organic compound toluene, and providing better measures for environmental pollution control. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Shown are X-ray diffraction spectra of cubic Ge-doped ZnSn(OH)6 prepared in Examples 1 to 12; in the figure, ZHS-1, ZHS-2, ZHS-3, ZHS-4, ZHS-5, ZHS-6, ZHS-7, ZHS-8, ZHS-9, ZHS-10, ZHS-11, and ZHS-12 represent the photocatalysts prepared in Example 1, Comparative Example 1, and Examples 3 to 12, respectively (the same below);

[0026] Figure 2 Shown is a scanning electron microscope image of the Ge-doped ZnSn(OH)6 photocatalyst of the present application;

[0027] Figure 3 Shown is a comparison of the XPS full spectra of Example 1 and Comparative Example 1;

[0028] Figure 4 The photocatalytic toluene removal activity test point-line graph of the products obtained in Examples 1 to 12 is shown; in the graph, the ordinate value represents the toluene activity percentage, and the removal rate is the difference before and after photocatalysis;

[0029] Figure 5 The figure shows the photocatalytic removal of toluene mineralization rate dot-line graph of the products obtained in Examples 1 to 12; in the figure, the vertical axis value represents the percentage of toluene mineralization rate, and the mineralization rate is the difference before and after photocatalysis;

[0030] Figure 6 The figure shows the photocatalytic removal of toluene activity test point-line graph of the product obtained in Comparative Example 1 under different concentrations of humid air; in the figure, the vertical axis value represents the toluene activity percentage, and the removal rate is the difference before and after photocatalysis (the same below);

[0031] Figure 7 The figure shows the photocatalytic activity test point-line graph of toluene removal of the product obtained in Example 1 under different concentrations of wet air;

[0032] Figure 8The figure shows the photocatalytic activity comparison of toluene of the products obtained in Example 1, Comparative Example 2 and Comparative Example 3; in the figure, ZHS-1, Ge-Ca, Ge-Ti represent the photocatalysts prepared in Example 1, Comparative Example 2 and Comparative Example 3 respectively (the same below);

[0033] Fig. 9 Shown is a dot-line graph of the stability test of photocatalytic removal of toluene pollutants in Example 1 within 335 minutes;

[0034] Fig.10 The electrical impedance comparison diagram of the product obtained in Example 1 and Comparative Example 1 and single GeO2 is shown;

[0035] Fig.11 The products obtained in Example 1 and Comparative Example 1 and the single product GeO2 capture e - Electron spin resonance spectrum of

[0036] Fig.12 Shown are the electron spin resonance spectra of the products obtained in Example 1, Comparative Example 1 and the single product GeO2 capturing ·OH. DETAILED DESCRIPTION

[0037] To facilitate the technical solution of the application, the following first provides a general description and definition of the terms and expressions involved in the application.

[0038] The terms "comprises", "includes" or any other variation thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus. In the absence of more restrictions, an element defined by the phrase "comprises a ..." does not exclude the presence of additional identical elements in the process, method, article or apparatus that includes the element.

[0039] In each group of comparative experiments provided in this application, unless otherwise specified, except for the differences indicated in each group, other experimental conditions, materials, etc. are kept consistent to ensure comparability.

[0040] Unless otherwise specified, the reagents and instruments used in the embodiments of the present invention can be purchased from the market.

[0041] The present invention uses SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, methyl cellulose and GeO2 as raw materials to prepare Ge-doped ZnSn(OH)6 photocatalyst by hydrothermal synthesis. The present invention uses the "crystallization-dissolution-recrystallization" mechanism to react in the hydrothermal synthesis: Zn 2+ +Sn 4+ +6OH- +Ge 4+ →ZnSn(OH)6 (containing Ge ions). The hydrothermal synthesis strategy has the characteristics of high crystallinity of the synthesized product, controllable product crystal size, and good uniform dispersion of the obtained powder. Ge ions are effectively incorporated into the ZnSn(OH)6 lattice at 160°C. The Ge-doped ZnSn(OH)6 photocatalyst prepared by this method has a single phase, and the photogenerated carriers are not easy to recombine and have a fast migration rate. A large number of electrons and hydroxyl radicals can be generated in a short time, thereby achieving efficient removal of volatile organic compounds in toluene and maintaining stable catalytic performance for a long time.

[0042] In the hydrothermal reaction in the reactor, water is used as the medium, and stirring helps to promote the rapid dissolution of SnCl4, Zn(Ac)2, and NaOH in water to form a large amount of Sn 4+ 、Zn 2+ OH -+ ions in a mixed solution, GeO2 can also be separated in a hydrothermal reaction at 160°C. 4+ ions, which facilitates Zn 2+ +Sn 4+ +6OH - +Ge 4+ →ZnSn(OH)6 (containing Ge ions) synthesizes ZnSn(OH)6 (containing Ge ions). The ordered assembly (such as micelle) formed in the solution by the subsequent addition of methylcellulose surfactant can effectively regulate the size and morphology of Ge-doped ZnSn(OH)6 nanoparticles. Thus, a photocatalyst with excellent mineralization performance for toluene is obtained.

[0043] The hydrothermal reaction temperature conditions of the present application are specifically as follows: the synthesis is carried out from room temperature to 160°C, and the temperature is kept at 160°C for 390min, and then cooled to room temperature. Controlling the hydrothermal synthesis temperature within the appropriate temperature and time range helps to ensure the high crystallinity of the ZnSn(OH)6 catalyst, the full reaction of the precursor, avoids the introduction of impurities, ensures high purity, and can effectively control the morphology and particle size of the material. If the synthesis temperature is too low, Ge ions cannot be incorporated into ZnSn(OH)6, the product contains unreacted precursors and intermediates, there is not enough energy to promote crystal growth, and some by-products may be generated, affecting the purity of the material. If the synthesis temperature is too high, it will not only increase energy consumption, but also may cause degradation of the material. In addition, under high temperature conditions, the crystal may grow too large, resulting in an increase in particle size, which is not conducive to material application. Rapid growth under high temperature conditions will also lead to an increase in internal stress of the crystal and reduce mechanical strength. If the holding time is too short, unstable phases will be generated and there will be too many defects inside the crystal; if the holding time is too long, the energy consumption cost will increase and it will also cause the transformation of ZnSn(OH)6 to Zn2SnO4.

[0044] In some embodiments of the present application, 0 to 1 g of GeO2 is added; in other embodiments of the present application, the mass of the added GeO2 is 0 g, 0.025 g, 0.05 g, 0.75 g, 0.1 g, 0.125 g, 0.25 g, 0.375 g, 0.5 g, 0.75 g or 1 g. Controlling the mass of the added GeO2 within a suitable range can save time and drugs, maximize economic benefits, and at the same time ensure that the obtained Ge-doped ZnSn(OH)6 photocatalyst has excellent photocatalytic performance for toluene;

[0045] In certain embodiments of the present application, the prepared Ge-doped ZnSn(OH)6 photocatalyst is further post-treated: after the prepared Ge-doped ZnSn(OH)6 photocatalyst is cooled, it is washed twice with distilled water and twice with anhydrous ethanol, and then dried at 60°C for 6 to 8 hours. The Ge-doped ZnSn(OH)6 photocatalyst is ground into fine particles to improve the strength and toughness of the material, increase its specific surface area, and improve the surface finish and precision of the material.

[0046] In some other embodiments of the present application, the present application proves through multiple characterization experiments that, compared with conventional unmodified ZnSn(OH)6, the Ge-doped ZnSn(OH)6 catalyst prepared in the present application has significantly higher photocatalytic (ultraviolet light) toluene activity than unmodified ZnSn(OH)6. Therefore, the present application also provides the use of the Ge-doped ZnSn(OH)6 photocatalyst prepared by the preparation method in removing toluene pollutants, or in the preparation of a photocatalytic product for removing toluene pollutants.

[0047] The following is a further description of the preparation method and application of a Ge-doped ZnSn(OH)6 photocatalyst provided in the present application.

[0048] Example 1: Preparation of highly active Ge-doped ZnSn(OH)6 photocatalyst

[0049] 4 mL of Zn(Ac)2·2H2O (0.5 M), 4 mL of SnCl4·5H2O (0.5 M), 4.6 mL of NaOH (3 M) and 0.125 g of GeO2 were added to a beaker containing 60 mL of distilled water, stirred at a stirring speed of 500-800 r / min for 5-10 min to obtain a white solution, and then 10 mL of methylcellulose (2.8 g·L -1 ), continue stirring for 5 to 10 minutes, add 40 mL of distilled water, and transfer the mixed solution into a stainless steel autoclave lined with Teflon. At this time, the concentration of Zn(Ac)2·2H2O in the reactor is 0.016M, the concentration of SnCl4·5H2O is 0.016M, the concentration of NaOH is 0.112M, and the concentration of methylcellulose is 0.23g / L. The reactor is sealed and placed in an oven for heating synthesis. The synthesis temperature is raised from room temperature to 160°C to 165°C (160°C in this embodiment), and the temperature is kept for 390 to 400 minutes (390 minutes in this embodiment), and then cooled to room temperature. After the reactor is cooled to room temperature, the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and then the precipitate is placed in an oven and dried at 55°C to 65°C (60°C in this embodiment) for 6 to 8 hours to finally obtain the product. Finally, the product was ground to obtain Ge-doped ZnSn(OH)6.

[0050] Example 2: Preparation of Ge-doped photocatalyst in comparative example

[0051] Comparative Example 1

[0052] The difference from Example 1 is that 0.125 g of GeO 2 added to the beaker containing 60 mL of distilled water is replaced by 0 g of GeO 2 .

[0053] Comparative Example 2

[0054] The difference from Example 1 is that ZnSn(OH)6 is replaced by CaCO3 (CAS No.: 471-34-1, reagent grade, 99%) of the same mass to obtain Ge-doped CaCO3.

[0055] Comparative Example 3

[0056] The difference from Example 1 is that ZnSn(OH)6 is replaced by TiO2 of the same mass (CAS No.: 13463-67-7, reagent grade, 99%) to obtain Ge-doped TiO2.

[0057] Example 3: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.015 g of GeO2.

[0058] Example 4: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.025 g of GeO2.

[0059] Example 5: The difference from Example 1 is that the 0.25 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.05 g of GeO2.

[0060] Example 6: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.075 g of GeO2.

[0061] Example 7: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.1 g of GeO 2。

[0062] Example 8: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.25 g of GeO2.

[0063] Example 9: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.375 g of GeO2.

[0064] Example 10: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.5 g of GeO2.

[0065] Example 11: The difference from Example 1 is that the 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 0.75 g of GeO2.

[0066] Example 12: The difference from Example 1 is that 0.125 g of GeO2 added to the beaker containing 60 mL of distilled water is replaced with 1 g of GeO2.

[0067] Example 13: The difference from Example 1 is that 4.8 mL of Zn(Ac)2·2H2O (0.5 M) is used to replace 4 mL of Zn(Ac)2·2H2O (0.5 M).

[0068] Example 14: The difference from Example 1 is that 4.6 mL of NaOH (3 M) is replaced by 5.5 mL of NaOH (3 M).

[0069] Example 15: The difference from Example 1 is that KOH is used to replace NaOH.

[0070] Example 16: Performance characterization experiment of different photocatalysts

[0071] A number of characterization tests were carried out using the photocatalysts of Examples 1 to 12, wherein Example 1 and Examples 3 to 12 can be abbreviated as ZHS-1, ZHS-3, ZHS-4, ZHS-5, ZHS-6, ZHS-7, ZHS-8, ZHS-9, ZHS-10, ZHS-11, and ZHS-12, respectively, and Comparative Examples 1 to 3 of Example 2 can be abbreviated as ZHS-2, Ge-Ca, and Ge-Ti in some test results.

[0072] Experiment 1: XRD characterization

[0073] In order to verify the types of ZHS-1 to 12, the present application uses a German Bruker D8 Advance X-ray diffractometer (CuKα, λ=0.154nm, working voltage and working current are 40kV and 40mA respectively) to perform XRD tests on each product. Figure 1 As shown, the XRD results show that the diffraction peaks of the products obtained in Examples 1 to 8 at 19.34°, 22.46°, 32.13°, 39.72°, 46.33°, 52.26° and 57.75° correspond to the ZnSn(OH)6 (JCPDS 74-1825) (111), (200), (220), (222), (400), (420) and (422) planes, respectively, and no other impurity peaks are found. However, with the increase of the doping amount, the peak intensity gradually decreases, and almost no peak is observed in ZHS-9 to ZHS-12. This indicates that the addition of excessive GeO2 will reduce the crystallinity of the material. In addition, all the diffraction peaks have slightly shifted to high diffraction angles. This may be due to the replacement of Sn atoms by Ge atoms, and the radius of Ge atoms is smaller than that of Sn atoms. The introduction of GeO2 changes the coordination environment of the crystal, causing the deformation of the lattice. According to the Bragg formula equation 2dsinθ=nλ, the interplanar spacing shows a decreasing trend, which further indicates that the successful introduction of Ge ions causes changes in the lattice structure.

[0074] Experiment 2: Electron microscopy characterization

[0075] The present application uses a Japanese JEOL Model JSM-6490 scanning electron microscope to characterize the sample morphology of Example 1. Figure 2 As shown, it can be found that the size of Ge-doped ZnSn(OH)6 is between 0.3 and 0.6 μm.

[0076] Experiment 3: XPS characterization

[0077] like Figure 3 As shown, the XPS full spectrum comparison diagram of Example 1 and Comparative Example 1 shows that in Example 1, 34.2 eV is assigned to Ge 3d, confirming that Ge ions have been doped into ZnSn(OH)6.

[0078] Experiment 4: Characterization of photocatalytic activity

[0079] The performance of the catalyst was evaluated by real-time monitoring of the instantaneous concentration of ppm-level volatile organic compounds (VOCs) in the reaction chamber using a photoacoustic spectrometer at room temperature. The specific operation is as follows: 4 samples of 0.1g were weighed on a 40mm×100mm rectangular rounded frosted glass sheet, evenly dispersed with a small amount of alcohol, and dried in a constant temperature drying oven at 60°C. After cooling to room temperature, the glass sheet loaded with the catalyst was placed in a rectangular continuous flow reaction chamber with a volume of 0.34L (200mm×100mm×17mm), and a layer of quartz glass was covered on the top of the reaction chamber to seal the reaction chamber (fixed with screws to prevent air leakage). At the same time, a 300W commercial mercury lamp was used above the reaction chamber as the ultraviolet light source for the photocatalytic reaction; the initial concentration of the pollutant was changed by adjusting the flowmeter on the gas line, and the flow rate of the humid air was set to 0.5L·min -1 , dry air flow rate (0.4L·min -1 ) and the flow rate of pollutants (0.1L·min -1 ) is 0.5L·min -1 , the diluted VOCs pollutant gas is introduced into the reaction chamber. Under dark conditions, after the catalyst reaches the adsorption-desorption equilibrium, the light is turned on to carry out the pollutant degradation reaction, and the toluene concentration in the reaction chamber is recorded using a photoacoustic spectrometer.

[0080] Figures 4 to 9 The photocatalytic activity diagram of toluene during the experiment. Figure 4It can be seen that the photocatalytic activity of Ge-doped ZnSn(OH)6 photocatalyst for 50ppm toluene oxidation is higher than 80%, and the toluene oxidation activity in Examples 1 and 4 to 10 is 100%, among which the toluene oxidation activity of Ge-doped ZnSn(OH)6 photocatalyst prepared in Example 1 quickly reaches 100% after about 10 minutes. It can be seen that the incorporation of Ge ions greatly improves the activity of ZnSn(OH)6, and the mineralization rate of toluene is about 120% ( Figure 5 ), showing its excellent deep mineralization ability for toluene and achieving effective conversion of toluene to CO2. In addition, in different wet air photodegradation tests of toluene, comparative example 1 has the highest degradation activity in 50% wet air, close to 83% ( Figure 6 ). However, in Example 1, the degradation of toluene in 50% humid air can reach 100% within 10 minutes, and the lowest can reach 80% ( Figure 7 ), it can be seen that Ge-doped ZnSn(OH)6 is less affected by water. We also tested the photocatalytic oxidation activity of 50ppm toluene prepared by the photocatalysts of Example 1, Comparative Examples 2 and 3. Figure 8 As shown, they are 100%, inactivated, decreased inactivity and then inactivated. This proves that Ge ion doping in wide bandgap semiconductors only works on ZnSn(OH)6, CaCO3 is inactive, and TiO2 is unstable. In addition, the present application has conducted a stability test on Example 1, as shown in FIG. Fig. 9 As shown, 100% activity was maintained in five cycle tests within 335 min without weakening, indicating that the Ge-doped ZnSn(OH)6 catalyst prepared by the hydrothermal method has excellent performance, good stability and extremely high efficiency.

[0081] Experiment 5: Electrochemical characterization

[0082] The present invention tests the impedance of Example 1, Comparative Example 1 and single GeO2. Fig.10 As shown, the results show that the impedance of Example 1 is much smaller than that of Comparative Example 1 and single GeO2 (the smaller the radius, the smaller the photocatalyst impedance), proving that the catalyst prepared in Example 1 can accelerate the migration rate of carriers and enhance the photocatalytic oxidation ability of toluene.

[0083] Test 6: Free Radical Test

[0084] like Fig.11As shown, by using the TEMPO spin-trapped electron EPR technique, the generation of electrons in Example 1, Comparative Example 1 and GeO2 alone under illumination was observed. It can be found that with the increase of the light-on time, the peak value of Example 1 decreases the fastest, which proves that after the introduction of Ge ions, ZnSn(OH)6 can generate more electrons and hydroxyl radicals and better activate toluene. The formation of ·OH is detected by the DMPO spin-trapped measurement method, as shown in FIG. Fig.12 As shown, with the increase of illumination time, the peak of Example 1 is particularly prominent, proving that the introduction of Ge ions can promote ZnSn(OH)6 to produce ·OH. ·OH helps the ring-opening reaction of toluene, converting toluene into benzoic acid intermediates. Benzoic acid has the lowest ring-opening energy barrier and can help toluene be completely mineralized into CO2; even under the attack of ·OH, toluene is directly converted into CO2 in one step.

[0085] The above specific implementation methods further illustrate the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above are only specific implementation methods of the present application and are not used to limit the protection scope of the present application. Any modifications, equivalent substitutions, improvements, etc. made on the basis of the technical solutions of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing Ge-doped ZnSn(OH)6 photocatalyst, characterized in that: Using SnCl4·5H2O, Zn(Ac)2·2H2O, alkali metal hydroxide, methyl cellulose and GeO2 as raw materials, Ge-doped ZnSn(OH)6 photocatalyst was prepared by hydrothermal synthesis. The specific preparation steps are as follows: a. Add SnCl4·5H2O, Zn(Ac)2·2H2O, alkali metal hydroxide, methyl cellulose and GeO2 to distilled water and stir to obtain a mixed solution; b. placing the mixture in a sealed pressure vessel for a hydrothermal reaction, and after the reaction is completed, cooling to room temperature, washing, drying and grinding to obtain Ge-doped ZnSn(OH)6 photocatalyst crystalline powder.

2. The preparation method according to claim 1, characterized in that: The alkali metal hydroxide is NaOH, KOH or LiOH.

3. The preparation method according to claim 2, characterized in that: The molar ratio of SnCl4·5H2O, Zn(Ac)2·2H2O, alkali metal hydroxide, and GeO2 is 1:1~1.2:7~8.4:0.07~4.

8.

4. The preparation method according to claim 3, characterized in that: The molar ratio of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and GeO2 is 1:1~1.2:7~8.4:0.12~4.

8.

5. The preparation method according to claim 3, characterized in that: The molar ratio of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and GeO2 is 1:1:7:0.

6.

6. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is raised from room temperature to 160°C to 165°C and then kept warm for 390min to 400min.

7. The preparation method according to claim 1, characterized in that: The stirring conditions are specifically: 500-800 r / min; 10-20 min.

8. The preparation method according to claim 1, characterized in that: The specific steps of washing are: cooling to room temperature and washing with distilled water and anhydrous ethanol twice each.

9. The preparation method according to claim 1, characterized in that: The drying conditions are specifically as follows: drying at 55° C. to 65° C. for 6 to 8 hours.

10. Use of the Ge-doped ZnSn(OH)6 photocatalyst prepared by the preparation method according to any one of claims 1 to 9 in removing toluene pollutants or preparing a photocatalytic product for removing toluene pollutants.

Citation Information

Patent Citations

  • Rare earth metal Ce-doped petal-shaped ZnO photocatalyst and preparation method thereof

    CN113694917A

  • Preparation method and application of zinc hydroxystannate photocatalyst

    CN116393118A

  • Preparation method of ZSH / SSH composite material and application of ZSH / SSH composite material in photocatalytic degradation of toluene

    CN117123210A

  • Heat-storing material composition, heat-storing body and heat-storing laminate

    JP2008063547A